MANAJEMEN KEMAHASISWAAN DALAM MENCIPTAKAN PERGURUAN TINGGI UNGGUL - Fachri, Moh; Mubarak, A Faizul; Subairi, Subairi (Managere: Indonesian Journal of Educational Management, 2021)
This paper aims to analyze the student management carried out by Nurul Jadid University in creating a superior university. This study uses a qualitative approach to the type of case study research. The data collection technique is done through interviews, observation, and documentation. The results showed that student management in creating superior universities at the University of Nurul Jadid Paiton Probolinggo was carried out through systematic planning involving the existing academic community. The planning is based on the results of internal and external analysis of the institution, which is followed up by determining the implementation strategy, program implementation, and evaluation system used for continuous improvement so that the institution's competitive advantage can be achieved.